2015
DOI: 10.1016/j.ijgo.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A study of an influenza A (H1N1)pdm09 outbreak in pregnant women in Rajasthan, India

Abstract: Influenza A (H1N1)pdm09 infection during pregnancy causes more severe illness. Early recognition and timely administration of antiviral therapy can improve outcomes. The role of influenza vaccination in this high-risk population cannot be overemphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Regarding seasonal influenza before the 2009 pandemic, pregnant women had a higher risk of influenza-related hospitalizations compared to non-pregnant or postpartum women, particularly in the late stages of pregnancy [ 11 , 12 ]. During the influenza A(H1N1)pdm09 pandemic, pregnancy was considered to be an independent risk factor for influenza severity and studies from different countries reported that pregnant women infected with the pandemic virus were more likely to experience hospitalizations [ 13 – 16 ], admission to intensive care units (ICU) [ 16 – 18 ], maternal mortality [ 19 23 ], and adverse neonatal outcomes [ 14 , 17 , 24 26 ]. During influenza seasons after the 2009 pandemic, pregnant women have had a higher risk than non-pregnant woman of being hospitalized due to respiratory illnesses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding seasonal influenza before the 2009 pandemic, pregnant women had a higher risk of influenza-related hospitalizations compared to non-pregnant or postpartum women, particularly in the late stages of pregnancy [ 11 , 12 ]. During the influenza A(H1N1)pdm09 pandemic, pregnancy was considered to be an independent risk factor for influenza severity and studies from different countries reported that pregnant women infected with the pandemic virus were more likely to experience hospitalizations [ 13 – 16 ], admission to intensive care units (ICU) [ 16 – 18 ], maternal mortality [ 19 23 ], and adverse neonatal outcomes [ 14 , 17 , 24 26 ]. During influenza seasons after the 2009 pandemic, pregnant women have had a higher risk than non-pregnant woman of being hospitalized due to respiratory illnesses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…H1N1 is a risk factor of hospitalization through pregnancy [7]. Bacterial pneumonia can happen as a pulmonary complication of H1N1 which developed a severe state, and can cause acute respiratory distress syndrome (ARDS), as a result [8].…”
Section: Discussionmentioning
confidence: 99%
“…Birth outcomes were also found to be potentially impacted by influenza infection during pregnancy, with fetal mortality ranging from 5.5% to 33% and prematurity rates from 20% to 33% [60]. A retrospective study conducted in a tertiary care center in Rajasthan led to the conclusion that mortality was significantly higher in pregnant women infected with 2009 influenza A H1N1 pandemic (A/H1N1pdm09) than in other infected women (36% vs. 17%) [61]. This is further supported by data from a retrospective analysis of 6203 A/ H1N1pdm09 cases from Rajasthan, as pregnancy was found to be the predominant predisposing factor [62].…”
Section: Maternal Influenza Vaccinationmentioning
confidence: 99%